Lenvatinib: an investigational agent for the treatment of differentiated thyroid cancer. (2nd September 2021) - Ferrari, Silvia Martina; Elia, Giusy; Ragusa, Francesca; Paparo, Sabrina Rosaria; Mazzi, Valeria; Miccoli, Mario; Galdiero, Maria Rosaria; Varricchi, Gilda; Foddis, Rudy; Guglielmi, Giovanni; Spinelli, Claudio; La Motta, Concettina; et al.
ABSTRACT: Introduction: Differentiated thyroid cancer (DTC; >90% of all TCs) derives from follicular cells. Surgery is the main therapeutic strategy, and radioiodine (RAI) is administered after thyroidectomy. When DTC progresses, it does not respond to RAI and thyroid-stimulating hormone (TSH)-suppressive thyroid hormone treatment, and other therapies (i.e. surgery, external beam radiation therapy and chemotherapy) do not lead to a better survival. Thanks to the understanding of the molecular pathways involved in TC progression, important advances have been done. Lenvatinib is a multitargeted tyrosine kinase inhibitor of VEGFR1-3, FGFR1-4, PDGFRα, RET, and KIT signaling networks implicated in tumor angiogenesis, approved in locally recurrent or metastatic, progressive, RAI-refractory DTC. Unmet needs regarding the patient clinical therapy responsiveness in aggressive RAI-refractory DTC still remain. Areas covered: We provide an overview from the literature of in vitro, in vivo and real-life studies regarding lenvatinib as an investigational agent for the treatment of aggressive TC. Expert opinion: According to the SELECT trial, the treatment should be initiated with a dosage of 24 mg/day, subsequently decreasing it in relation to the side effects. The decision making process in patients with aggressive RAI-refractory DTC should be personalized and the potential toxicity should be properly managed.